IMPLEMENTASI PEMBELAJARAN BACA TULIS AL-QUR’AN DI SMP RADEN RAHMAT BALONGBENDO SIDOARJO - Amir Zain, Lubabul; Surur, Shobihus; Said, Ali (Program Studi Pendidikan Agama Islam, Fakultas Agama Islam, Universitas Hasyim Asy'ari Tebuireng Jombang, Indonesia, 2023)
Abstract: Learning to Read and Write the Qur'an or what is often abbreviated as BTQ, is now very necessary. Moreover, most of the children at the age after graduating from basic education or more precisely when they were already at the junior high school level (SMP) had started to stop studying anymore. This is based on several factors. Among them, there is a sense of prestige, too many outside activities, and feeling that if they have reached the level of the Qur'an in the place of reciting they think they are capable and finished reciting it. This is of course very concerning considering that they are the next generation of Islam as well as the nation's successor. So with this BTQ learning, it is hoped that it can be a solution for the above phenomenon. This research was conducted at Raden Rahmat Balongbendo Middle School, Sidoarjo. The research objectives are to describe:. Implementation of AlQur'an Reading and Writing Learning at Raden Rahmat Balongbendo Middle School Sidoarjo. This study used descriptive qualitative method. The researcher is the main instrument, by acting as a passive observer. The data used are primary and secondary data. Collecting data used through observation, interviews and documentation. Checking the validity of the data used is triangulation of sources and methods. The conclusions of this study are (1) Learning at Raden Rahmat Balongbendo Junior High School which uses the classical method of drill followed by an evaluation method of learning through talaqqi. (2) Implementation of AlQur'an Reading and Writing Learning at Raden Rahmat Balongbendo Middle School can be seen in the readings of students who are considered to meet the standards according to the rules of recitation. (3) Supporting Factors, namely: a good explanation from the principal and teachers, assisted by the AlQur'an Study Program (PSQ) team, foundation administrators, and high student motivation; Inhibiting factors, namely: weak student learning, input factors that come in and various backgrounds, obstacles due to the pandemic period yesterday made some students, especially grade 9 students, now have to be fast in catching up on material that was left behind.